Answer:
okay I need help please
Step-by-step explanation:
find cos b in the triangle
Answer: 60
Step-by-step explanation:
Area = ½base × height
600 = ½b × 20
600/20 = ½b
Base = 30 × 2
Answer:
1
Step-by-step explanation:
To solve this, first, take 22 minutes and divide it by 60 minutes, which is the number of minutes in an hour. Then, add two to the value, and multiply it by six square meters per hour, which is the rate that David can paint the wall. From there, you get 14.2 square meters which he painted in 2 hours and 22 minutes. Divide 14.2 square meters by the length of 11 meters to get 1.290 meters. Since they asked you to round to the nearest meter, you get 1 meter.
When you are multiplying an exponent directly into a number/variable with an exponent, you multiply the exponents together.
For example:
![(x^{2} )^{3} = x^6](https://tex.z-dn.net/?f=%28x%5E%7B2%7D%20%29%5E%7B3%7D%20%3D%20x%5E6)
![(x^{3} )^5=x^{15}](https://tex.z-dn.net/?f=%28x%5E%7B3%7D%20%29%5E5%3Dx%5E%7B15%7D)
When you are multiplying a variable with an exponent by another variable with an exponent, you add the exponents together.
For example:
![(x^{2} )(x^{3})=x^{5}](https://tex.z-dn.net/?f=%28x%5E%7B2%7D%20%29%28x%5E%7B3%7D%29%3Dx%5E%7B5%7D)
![(x^{1} )(x^{2})=x^{3}](https://tex.z-dn.net/?f=%28x%5E%7B1%7D%20%29%28x%5E%7B2%7D%29%3Dx%5E%7B3%7D)
![(\frac{(x^{-3})(y^{2})}{(x^{4})(y^{6})} )^{3}=\frac{(x^{-9})(y^{6})}{(x^{12})(y^{18})}](https://tex.z-dn.net/?f=%28%5Cfrac%7B%28x%5E%7B-3%7D%29%28y%5E%7B2%7D%29%7D%7B%28x%5E%7B4%7D%29%28y%5E%7B6%7D%29%7D%20%29%5E%7B3%7D%3D%5Cfrac%7B%28x%5E%7B-9%7D%29%28y%5E%7B6%7D%29%7D%7B%28x%5E%7B12%7D%29%28y%5E%7B18%7D%29%7D)
You multiply 3 into each exponent in the numerator and the denominator
![\frac{(x^{-9})(y^{6})}{(x^{12})(y^{18})}= \frac{y^{6}}{(x^{9})(x^{12})(y^{18})}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%5E%7B-9%7D%29%28y%5E%7B6%7D%29%7D%7B%28x%5E%7B12%7D%29%28y%5E%7B18%7D%29%7D%3D%20%5Cfrac%7By%5E%7B6%7D%7D%7B%28x%5E%7B9%7D%29%28x%5E%7B12%7D%29%28y%5E%7B18%7D%29%7D)
When you have a negative exponent, you move it to the other side of the fraction to make the exponent positive.
![\frac{y^{6}}{(x^{21})(y^{18})} = \frac{1}{(x^{21})(y^{12})}](https://tex.z-dn.net/?f=%5Cfrac%7By%5E%7B6%7D%7D%7B%28x%5E%7B21%7D%29%28y%5E%7B18%7D%29%7D%20%3D%20%5Cfrac%7B1%7D%7B%28x%5E%7B21%7D%29%28y%5E%7B12%7D%29%7D)
When you have something like this:
![\frac{x^{2}}{x^5}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D%7D%7Bx%5E5%7D)
You subtract the exponents together, so:
![\frac{x^2}{x^5} = x^{2-5} = x^{-3} = \frac{1}{x^3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E2%7D%7Bx%5E5%7D%20%3D%20x%5E%7B2-5%7D%20%3D%20x%5E%7B-3%7D%20%3D%20%5Cfrac%7B1%7D%7Bx%5E3%7D)
Your answer is the second option
Answer:
- 8p - 80
Step-by-step explanation:
Given
4(- 15 - 3p) - 4(- p + 5) ← distribute both parenthesis
= - 60 - 12p + 4p - 20 ← collect like terms
= - 8p - 80